MEMBANGUN SIKAP SOSIALANAK MELALUI PERMAINAN TRADISIONAL - Mariani, Ni Nyoman (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2017)
Traditional games, especially traditional Balinese games have been abandoned, one reason is the rapid development of technology in various aspects of life, one of them is digital games. Traditional games actually have many benefits for children, indirectly children will be stimulated to be creative and very good for the physical and psychological training of children. It is part of the character education process, so the traditional games can be started early. In the traditional games, students are able to build social attitude, such as social ability to work together, compact, have democratic attitude and love attitude environment. social attitude is expected to facilitate or provide opportunities for positive development of children, then they will be able to achieve social development in a mature. On the contrary, if the social environment is less conducive, the social attitude of the children tend to display deviant behavior. For that, the development of a social attitude of children through traditional games is needed.